2023
DOI: 10.1055/a-2048-7486
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Postoperative Dressing in Hypospadias Surgery: A Systematic Review and Meta-analysis of the Pediatric Literature

Abstract: Introduction: This study aimed to describe the available dressings and their management in patients undergoing hypospadias repair and compare post-operative outcomes with and without dressing and between the different dressing types. Materials and Methods: A comprehensive electronic literature search of PubMed, Embase, and Cochrane Library was conducted to obtain studies, published in the period 1990-2021, reporting on the dressing used following hypospadias surgery. All information regarding the dressing were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…However, some authors suggest that excessive pressure could interfere with blood flow and cause complications. A recent meta-analysis by the Naples team concluded that there is no quality evidence in favor of one option or the other, and that it cannot be claimed that not using any type of dressing proves beneficial in any way (7) . Therefore, the choice in terms of dressing should be made at the surgeon's discretion and according to patient needs.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors suggest that excessive pressure could interfere with blood flow and cause complications. A recent meta-analysis by the Naples team concluded that there is no quality evidence in favor of one option or the other, and that it cannot be claimed that not using any type of dressing proves beneficial in any way (7) . Therefore, the choice in terms of dressing should be made at the surgeon's discretion and according to patient needs.…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, algunos autores defienden que una presión excesiva podría interferir con el riego sanguíneo y provocar complicaciones. Un reciente metaanálisis del equipo de Nápoles concluye que no hay evidencia de calidad a favor de una opción y otra y que no pueden afirmar que el no poner ningún tipo de vendaje suponga un beneficio (7) . Finalmente afirman que ha de quedar a la elección del cirujano el vendaje que más se adecue a las necesidades de cada paciente.…”
Section: Discussionunclassified